PEMBUATAN GAME 2D HORROR “BLACK, WHITE, AND …” DENGAN PLATFORM WINDOWS - Kevin, Kevin; Pragantha, Jeanny; Haris, Darius Andana (Jurnal Ilmu Komputer dan Sistem Informasi, 2022)
"Black, White And ..." is a 2D Horror game with a sub-genre psychological horror game developed for Windows PC. This game was made using Unity as the game engine with C# as the programming language. In this game, the player will play as an amnesiac girl who has just awoken. The goal of this game is to search for a way out from the strange black and white world. The player will have to survive from the enemy and traps with the ability to move from the black world to the white world and vice versa. to ward the enemies, the player had to scream. The game has implemented a Voice Recognition feature to differentiate between scream or not scream. The testing has been done by using blackbox testing, alpha testing, and beta testing method. The test results show that most of the respondents experience a sense of fear and tension as well as the intention to play the game again.